PRA Melting-ICE Project: Svalbard 2022 Expeditions Report [version 1; peer review: 2 approved] - Enrico Maiero; Elisa Baldrighi; Riccardo Cerrato; Delia Segato; Massimiliano Vardè; Mauro Mazzola; Iain Rudnik; James Bradley; Margaret Cramm; Angelina Cordone; Stefano Caliro; Donato Giovannelli; et al. (Open Research Europe)
Arctic regions are among the fastest warming areas of the planet. Increasing average temperatures over the last five decades have deepened the thawing of the upper-most layer of permafrost across the Arctic, which contains significant amounts of organic carbon. The progressive deepening of seasonal thawing releases carbon that is used by active microorganisms which also produce greenhouse gases, potentially onsetting a positive feedback on global warming. Despite their importance in controlling organic matter degradation and greenhouse gas fluxes to the atmosphere, there is a lack of data on activity and dynamics of microbial communities in High Arctic soils in response to seasonal thaw. This report describes three specific expeditions performed on the Svalbard archipelago, carried out within the framework of the PRA (Italian Arctic Research Program) project Melting-ICE, performed between February and October 2022, reporting site characteristics and samples collected. The project aims to investigate the diversity and activity of active layer microbial communities across a full season thaw cycle, correlating microbial diversity with gas fluxes and composition. During these expeditions, a total of eight different sites were selected to investigate the microbiology and geochemistry of soils, as well as to estimate the gas fluxes from the soil to the atmosphere. The data collected in the field, combined with the results obtained in the laboratory, will provide a snapshot of the seasonal activity of the microbial communities present in the permafrost’s active layer. The three campaigns will provide data to estimate the impact of permafrost melting on the carbon cycle and the role of microorganisms in the release of greenhouse gases.